A multicenter prospective audit to investigate the current management of patients undergoing anti-reflux surgery in the UK: Audit & Review of Anti-Reflux Operations & Workup. Issue 7 (16th January 2021) - ,; Walker, Rob; Wiggins, Tom; Blencowe, Natalie S; Findlay, John M; Wilson, Michael; Currie, Andrew C; Hornby, Steve; Markar, Sheraz R; Rahman, Saqib; Lloyd, Megan; Hollyman, Marianne; et al.
Abstract: Background: There are a variety of surgical and endoscopic interventions available to treat gastroesophageal reflux disease. There is, however, no consensus on which approach is best. The aim of this national audit is to describe the current variation in the UK clinical practice in relation to anti-reflux surgery (ARS) and to report adherence to available clinical guidelines. Methods: This national audit will be conducted at centers across the UK using the secure online web platform ALEA. The study will comprise two parts: a registration questionnaire and a prospective multicenter audit of ARS. All participating centers will be required to complete the registration questionnaire comprising details regarding pre-, peri-, and post-operative care pathways and whether or not these are standardized within each center. Following this, a 12-month multicenter prospective audit will be undertaken to capture data including patient demographics, predominant symptoms, preoperative investigations, surgery indication, intraoperative details, and postoperative outcomes within the first 90 days. Local teams will retain access to their own data to facilitate local quality improvement. The full dataset will be reported at national and international scientific congresses and will contribute to peer-reviewed publications and national quality improvement initiatives. Conclusions: This study will identify and explore variation in the processes and outcomes following ARS within the UK using a collaborative cohort methodology. The results generated by this audit will facilitate local and national quality improvement initiatives and generate new possibilities for future research in anti-reflux interventions.